Pencegahan dan Penanganan Keterlambatan Berbicara Pada Anak - Amanda Eka Putri; Nandini Febriani; Ananda Nora Nopriani; Muhammad Asif Rasyhad; Beny Rahim (PUSAKO : Jurnal Pengabdian Psikologi, 2024)
Speech is part of a child's development that starts from birth. A child not being able to understand and repeat about 20 important words at the age of one and a half years is one of the symptoms of developmental disorders, to be precise, speech delay. This condition can still develop, it's just that the time is slower than the average child. Therefore, it is necessary to conduct psychoeducation to provide knowledge to the general public (18-80 years old) about the causes and effects of speech delay in early childhood. This psychoeducation is motivated by questionnaire data which shows the results that most respondents do not have an awareness of the existence of speech delay disorders in children. To respond to this, the researcher designed a 7-minute 54-second psychoeducational video that was aired for five days as a method that aims to increase the understanding of the general public to prevent speech delay. After watching the psychoeducational video, respondents were given an online form containing 10 post-test questions with 20 respondents.